Urtica dioica Effect on Malonyl-CoA Decarboxylase - Qujeq; Tatar; Feizi; Parsian; Halalkhor (Avicenna Journal of Medical Biochemistry, 2014)

(untitled)
Background The malonyl-CoA decarboxylase (MCD, EC.4.1.1.9) enzyme regulates malonyl-CoA levels. The effect of aerial parts extracts of Urtica dioica (UD) on MCD is poorly understood.